THE EFFECTIVENESS OF THE SUSAN LOUCKS-HORSLEY (SLH) LEARNING MODEL VIEWED FROM THE SKILLS OF THE SCIENCE PROCESS - Ade Ogi Prayoga; Andi Thahir; Irwandani Irwandani (Jurnal Pendidikan Fisika, 2020)
Science process skills are the basis for the foundation of logical thinking. Therefore science process skills (KPS) need to be owned by students. The purpose of this study, is to see the effectiveness of using SLH (Susan Loucks-Horsley) learning models in terms of science process skills (KPS) for grade VIII students on the subject of light and optical devices. The subjects of this study were 61st grade students of SMP Negeri 1 Banyumas with 61 students. The research method used is a quasi-experimental design with a non equivalent control group. The research sample consisted of two classes, namely the experimental class and the control class. The research data were obtained by using descriptive questions and observation sheets for the science process skills. Based on the results of the hypothesis test, the research results can be concluded that the use of the SLH (Susan Loucks-horsley) learning model is effective in improving students' science process skills. The application of the SLH model can be used as a solution to improve science process skills, because the SLH model starts from a context that motivates students to use their initial knowledge, then learners learn in groups to learn the material independently.